Membentuk Keluarga Tangguh dalam Merawat Penderita Gangguan Jiwa dengan “Peer Group Course” - Dian Pitaloka Priasmoro; Dimas Ilham PI; Indra Susanto (Yayasan Inspirasi El Burhani, 2022)
Introduction: Anxiety that arises in families of people with mental disorders can be caused by the patient's behavior that is not like a normal person so that it makes excessive worry. Efforts that can be made are reducing anxiety by providing calm, listening to complaints that cause anxiety, and teaching guided imagery techniques. Objective: The purpose of the service activity is to form a strong family in caring for patients with peer group families to reduce family anxiety Method: The method used in this program is lecture and practice. The target of this activity is 32 families who are the main care givers for people with schizophrenia in the Ampelgading Community Health Center, Malang. In session one, participants were given material about peer groups including identify, quick coping, breathing and guided imagery and in stage two the team teaches participants to practice guided imagery accompanied by music. Result: The results were obtained from 32 primary care givers, 18 people (56%) of whom experienced moderate to severe anxiety obtained through filling out the RAT (Rapid Anxiety Test) questionnaire. Next in session 1 all participants were given material about anxiety and how to reduce it. Results on session 1 all participants can re-explain the content of the material, then in session 2 the team teaches participants to practice the steps including Identify, Quick Copping, Breathing, and Guided imagery. The results obtained from this 2nd session, participants can follow the instructions given below given the team up to the formation of groups besides that there are several participants who crying because I feel relieved to be able to pour out the anxiety that is faced while being a care giver ± last 3 years. Conclusion: In conclusion, it is very important for families to be proactive in seeking psychological support and assistance to their closest family and community.